Distal coronary artery abnormalities in Kawasaki disease: experience on CT coronary angiography in 176 children. (8th April 2022) - Singhal, Manphool; Pilania, Rakesh Kumar; Jindal, Ankur Kumar; Gupta, Aman; Sharma, Avinash; Guleria, Sandesh; Johnson, Nameirakpam; Maralakunte, Muniraju; Vignesh, Pandiarajan; Suri, Deepti; Sandhu, Manavjit Singh; Singh, Surjit
Abstract: Objective: Precise evaluation of coronary artery abnormalities (CAAs) in Kawasaki disease (KD) is essential. The aim of this study is to determine role of CT coronary angiography (CTCA) for detection of CAAs in distal segments of coronary arteries in patients with KD. Methods: CTCA findings of KD patients with distal coronary artery involvement were compared with those on transthoracic echocardiography (TTE) during the period 2013–21. Results: Among 176 patients with KD who underwent CTCA (128-Slice Dual Source scanner), 23 (13.06%) had distal CAAs (right coronary—15/23; left anterior descending—14/23; left circumflex—4/23 patients). CTCA identified 60 aneurysms—37 proximal (36 fusiform; 1 saccular) and 23 distal (17 fusiform; 6 saccular); 11 patients with proximal aneurysms had distal contiguous extension; 9 patients showed non-contiguous aneurysms in both proximal and distal segments; 4 patients showed distal segment aneurysms in absence of proximal involvement of same coronary artery; 4 patients had isolated distal CAAs. On TTE, only 40 aneurysms could be identified. Further, distal CAAs could not be identified on TTE. CTCA also identified complications (thrombosis, mural calcification and stenosis) that were missed on TTE. Conclusions: CAAs can, at times, occur in distal segments in isolation and also in association with, or extension of, proximal CAAs. CTCA demonstrates CAAs in distal segments of coronary arteries, including branches, in a significant number of children with KD—these cannot be detected on TTE. CTCA may therefore be considered as a complimentary imaging modality in children with KD who have CAAs on TTE.